2019
DOI: 10.1108/ijshe-01-2019-0017
|View full text |Cite
|
Sign up to set email alerts
|

The participatory process of planning social and environmental responsibility at a Brazilian university

Abstract: Purpose Universities have an important role in articulation of the transformation of society, in the formation of individuals capable of acting in the processes that enable sustainable development goals (SDGs), in theoretical areas and in practical and concrete actions. Within the University of Passo Fundo (UPF), Brazil, some practices are being adopted from this perspective. This paper aims to present the efforts of UPF to achieve SDGs in its activities. Design/methodology/approach For the development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…The findings from 15 empirical studies have suggested that solving social problems was a top priority for universities in emerging economies. With regards to issues such as human rights, the work environment must aim to change and foster stakeholders' perceptions of the HEI (El-Kassar et al , 2019; Frandoloso and Rebelatto, 2019). In fact, when discussing a university's social responsibilities, pressure from its local society has unintentionally created barriers as well as opportunities with regard to USR implementation (El-Kassar et al , 2019; Kouatli, 2019b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from 15 empirical studies have suggested that solving social problems was a top priority for universities in emerging economies. With regards to issues such as human rights, the work environment must aim to change and foster stakeholders' perceptions of the HEI (El-Kassar et al , 2019; Frandoloso and Rebelatto, 2019). In fact, when discussing a university's social responsibilities, pressure from its local society has unintentionally created barriers as well as opportunities with regard to USR implementation (El-Kassar et al , 2019; Kouatli, 2019b).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, when comparing research between Lebanese and Colombian universities, El-Kassar et al (2019) stressed that USR is considered an excellent marketing tool that aims to enhance university image and student loyalty (El-Kassar et al , 2019). Relying on the provisions of the law, Brazilian universities adhere to and define exactly how important an educational institution's role is in focusing on their local community issues and aiming to meet sustainable development goals (Frandoloso and Rebelatto, 2019). Thus, serving the local community through student volunteering and participation in knowledge transfer from academics and students to the local community has become widely popular and the benefits are undeniable.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies are devoted to the exploration of social responsibility for regional development in some African countries (Mbah & Charles, 2019;Fiarmonti, 2013;Fongwa & Wangenge-Ouma, 2015). Different practices of a Brasilian university in the frame of regional development were examined on planning social and environmental responsibility (Frandoloso & Rebelatto, 2019). It was noted that regional management of areas supports actions (integration between the university and the community) directed to the urban sprawl in the nearest territories of a university in Indonesia (Giyarsih, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Universities have an important role to play in articulating the transformation of society, in the formation of individuals capable of acting in the processes that will allow the sustainable development goals (SDGs) to be reached, in theoretical areas and in practical and concrete actions (Frandoloso and Gasparetto Rebelatto, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%